Role of Continuous Professional Development for English Language Teachers in Enhancing Teaching Public Ordinary Secondary Schools. - Bakar, Bakar Moh’d; Mandila, Dr. Timothy; Koda, Dr. Gadi (International Journal of Scientific Research and Management (IJSRM), 2025)
The study aimed to investigate the role of continuous professional development for English language teachers in enhancing teaching of two students in a public ordinary secondary school in Pemba Island, Zanzibar. This study was guided by the Zone of Proximal Development (ZPD) theory, developed by Vygotsky and utilised a convergent design under methods. The target population comprised 585 individuals, including 420 English teachers, 25 subject inspectors, and 140 school heads. Systematic, purposive, and stratified sampling techniques were used to obtain a sample of 42 schools, 21 school heads, 20 school inspectors, and 126 English subject language teachers, heads of schools, making a total sample of 167 respondents. The study used questionnaires, interview guides and focus group discussion methods for data collection. The researcher determined the validity of the instruments using two research experts. The reliability of Likert scale items was determined through Cronbach's Alpha, and the coefficient for teachers of the English language subject was 0.78, respectively. Peer review and triangulation were used to assess the dependability of the qualitative instruments. Quantitative data were analysed using descriptive and inferential statistics, and qualitative data were analysed thematically. The study revealed that the majority of English language subject teachers agree that continuous professional development enhances teaching of form two in public ordinary secondary schools. Based on the findings, the study concludes that continuous professional development of English language teachers enhances the learning of Form Two students in Pemba Island. The studies suggest that to enhance continuous professional development for English language teachers to improve teaching of Form Two students in public ordinary secondary schools, the Ministry of Education and Vocational Training should establish ongoing professional development programs that allow teachers to reflect on their practices and identify growth areas.